Analysis of the changes of bacterial spectrum and drug resistance in sputum culture of ICU children in a hospital of pediatric in Jiangsu Province from 2017 to 2022 - Huang, H; Wei, J; Shen, H J; Tan, Q X; Xue, J; Wang, C (Zhōnghuá yùfáng-yīxué zázhì, 2024)
To investigate the changes of the distribution and drug resistance profile of bacteria from ICU children with lower respiratory tract infection (LRTI) in Suzhou City, Jiangsu Province from 2017 to 2022. From January 2017 to December 2022, a cross-sectional observational study on the bacterial spectrum analysis among intensive care unit (ICU) children with LRTI was conducted in Children's Hospital of Soochow University. The bacteria was cultivated by culture methods from sputum samples, and identified by MALDI-TOF mass spectrometry. Drug sensitivity tests were performed by the VITEK2 Compact fully automated analysis system and the paper slide method. The test or Fisher's exact probability was used to analyze the changes of the distribution of sputum culture-positive bacteria and drug resistance in ICU children. The overall detection rate of sputum culture was 42.06% (1 182/2 810). (25.63%,303/1 182), (13.62%,161/1 182) and (13.28%,157/1 182) were the top three. Proportions of (17.90% 11.02%, ²=11.17, =0.001),